Interhemispheric vs. stimulus-response spatial compatibility effects in bimanual reaction times to lateralized visual stimuli - Pellicano, Antonello; Barna, Valeria; Nicoletti, Roberto; Rubichi, Sandro; Marzi, Carlo Alberto (Frontiers in Psychology, 2013)
In the present study, we tested right- and left-handed participants in a Poffenberger paradigm with bimanual responses and hands either in an anatomical or in a left-right inverted posture. We observed a significant positive crossed-uncrossed difference (CUD) in reaction times for both manual dominance groups and both response postures. These results rule out an explanation of the CUD in terms of stimulus-response spatial compatibility and provide convincing evidence on the important role of interhemispheric callosal transfer in bimanual responding in right- as well as left-handed individuals.